Case Report: First Report of Fatal Legionella pneumophila and Klebsiella pneumoniae Coinfection in a Kidney Transplant Recipient - Scaturro, Maria; Girolamini, Luna; Pascale, Maria Rosaria; Mazzotta, Marta; Marino, Federica; Errico, Giulia; Monaco, Monica; Girolamo, Antonietta; Rota, Maria Cristina; Ricci, Maria Luisa; Cristino, Sandra (Frontiers in Medicine, 2022)
A very rare case of pulmonary Klebsiella pneumoniae-Legionella pneumophila co-infection in a double kidney transplanted man affected by chronic renal disease is described. Cases of Legionnaires' disease with an incubation period of 14 days have rarely been documented. Despite the long period of hospitalization, typing of clinical and environmental Legionella pneumophila strains demonstrated that patient’s home water distribution system was the source of infection, highlighting as Legionella house contamination can be a hidden risk, especially for immune-compromised people.